Research in paralympic xc-skiing - Gastaldi, L. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
Over the years, adapted cross country skiing (XC-skiing) has quickly grown from a form of physical therapy and medical rehabilitation for veterans to a gratifying recreational pursuit for individuals of all ages and disability. Predictably, recreation gave birth to agonistic sport. Disabled XC-skiing is, since its first appearance in Ornskoldsvik games in 1976, a dominant sport in the winter Paralympic games. Currently XC-skiers with disabilities compete, under the rules of the International Paralympic Committee (IPC), in three medal categories: visually impaired, locomotor standing and sitting, The increasing popularity of XC-skiing, unfortunately, has not encouraged significant scientific research. The aim of this lecture is to take stock of the research in Paralympic XC-skiing.